Real-Time GSM Broadcast Receiver on a Cortex-M4 Microcontroller - Erhardt, Stefan; Pflaum, Felix; Weigel, Robert; Kölpin, Alexander (Radio & Wireless Week, 2018)
Recent microcontrollers provide enough computing power to perform signal processing while still being energy efficient and enable more flexibility than FPGAs. A fully functional GSM broadcast receiver was implemented on a Cortex-M4 microcontroller that is able to decode broadcast control channel (BCCH) messages. With several algorithmic optimizations it is able to operate in real-time in combination with a Sub-GHz transceiver as RF front-end. The timing was proven by measurements with an logic analyzer.